Pengaruh lama dan suhu pemanasan serta pengecilan ukuran terhadap mutu puree pisang talas (Musa paradisiacal var sapientum L.) - Rini Hustiany; Febriani Purba; Febi Nuradina; Siti Turana (Agroindustrial Technology, University of Trunojoyo Madura, 2023)
The talas banana is the superior local fruit of South Kalimantan. Talas bananas are still utilized in a few of applications and are mostly consumed fresh. Talas bananas have a particular aroma that no other banana has. This study aimed to analyze the effect of heating time, temperature, and size reduction on talas banana puree's sensory and chemical quality. The heating temperatures used were 70, 90, and 121oC. The heating time for 70 and 90oC was 15, 20, and 25 minutes, while for 121oC was 2, 4, and 6 minutes. The effect of size reduction was coarse texture (30 seconds) and fine texture (1 minute). Talas banana puree was analyzed by scoring test (color, texture, aroma, and taste) and chemical test (moisture content, pH, total dissolved solids, total titrated acid, reducing sugar content, and protein content). Data were analyzed using Analysis of Variance (ANOVA) with a nested factorial randomized block design at temperature with a further test was Duncan's test with α=5%. Sensory quality data were analyzed by the Kruskal Wallis test at α=5%, followed by the Tukey test at α= 5%. Talas banana puree is light yellow, close to the soft, banana aroma, and sweet taste. The best results for talas banana puree were obtained at 70oC with a 15-minute heating time and a 1-minute size reduction, 90oC with a 15-minute heating time and a 1-minute size reduction, and 121oC with a 6-minute heating time and a 1-minute size reduction.